Rebalancing our regulatory response to Deepfakes with performers' rights. (August 2021) - Pavis, Mathilde
Law experts have been actively looking for solutions within the law to control Deepfakes since their emergence in 2017. This article puts forward performers' rights as a suitable regulatory tool for Deepfakes, defined as synthetic performances produced using artificial intelligence systems. In many respects, performers' rights represent a more sophisticated response to the challenges posed by Deepfake technology compared to existing legal remedies and reform proposals introduced to regulate Deepfakes. In making its case for performers' rights as suitable regulatory response to Deepfakes, this article uncovers a tension: performers' rights are an attractive solution to regulate Deepfakes but this technology challenges their scope of application. This is because Deepfakes uses content protected by performers' rights (performances) in a way unforeseen by intellectual property policy-makers at the time these rights were introduced into law. Despite this limitation, performers' rights remain one of the most attractive legal remedies in regulating Deepfakes, if adequately reformed. This article proposes two routes for the reform of performers' rights to address this gap. The first involves an ad hoc modification of performers' rights to ensure that performances manipulated by Deepfakes are covered. The second and preferred recommendation replaces the regime of performers' rights with a regime of performers' copyright. This small, yet important, change in legal regimes can be the difference between piecemeal, uneven and, therefore, ineffective protection against unauthorized Deepfakes and a harmonized international approach to the technology.